Cytotoxic effect of a 35% hydrogen peroxide bleaching gel on odontoblast-like MDPC-23 cells - Dias Ribeiro, Ana Paula [UNESP]; Sacono, Nancy Tomoko [UNESP]; Rosetti Lessa, Fernanda Campos [UNESP]; Nogueira, Indri [UNESP]; Coldebella, Carmen Regina [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Mosby-elsevier, 2009)
Objective. This study evaluated transenamel and transdentinal cytotoxic effects of a bleaching gel on the MDPC-23 cell line.Study design. Discs obtained from bovine incisors were placed in a metallic device to simulate an in vivo pulp chamber. Groups were formed according to the enamel surface treatment: G1: 35% H(2)O(2) bleaching gel; G2: 35% H2O2 bleaching gel + halogen light; G3: halogen light; and G4: control. Cell metabolism was evaluated by the methyltetrazolium assay and cell morphology by scanning electron microscopy.Results. Cell metabolism decreased by 31.7%, 41.6%, and 11.5% in G1, G2, and G3, respectively. Cytotoxic effects observed in G2 were significantly more severe compared with G3 and G4. In G1 and G2, a smaller number of viable cells with major morphologic alterations remained adhered to dentin.Conclusion. The bleaching gel associated with light presented transenamel and transdentinal cytotoxic effects characterised by direct damage to odontoblasts and decrease of their metabolic activity. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2009; 108: 458-464)